Comparative evaluation of the effectiveness and safety of trichloroacetic acid chemical reconstruction of skin scars versus microneedling in facial atrophic acne scars - Silpi Lakra; Pdiangty Giri Mawlong; Nishant Bisht (Asian Journal of Medical Sciences, 2025)
Background: Acne vulgaris is a common skin condition that affects numerous adolescents and young adults, often resulting in atrophic acne scars that can cause significant psychological distress for many individuals. Aims and Objectives: The primary objective of this study is to assess the effectiveness and safety of trichloroacetic acid (TCA) chemical reconstruction in comparison to microneedling for the treatment of atrophic acne scars. Materials and Methods: In this study, patients with facial atrophic acne scars were randomly assigned to one of two groups, each consisting of 20 participants. They received either TCA chemical reconstruction of skin scars (CROSS) or microneedling treatment at 4-week intervals for 16 weeks. The final outcomes were assessed 4 weeks following the last treatment session. Various evaluation methods were employed, including Goodman and Baron’s qualitative and quantitative acne scarring grading systems, the physician’s global assessment (PGA), and a visual analog scale to measure treatment results in both groups. Additionally, any side effects were documented during each visit. Results: On completion of the treatment, there was a notable enhancement in the qualitative acne scar grades, as assessed by Goodman and Baron, alongside a reduction in the mean quantitative acne scar scores. The percentage decrease in these scores, as well as the evaluations from PGA and visual analog scales, showed comparable results across both groups, with no significant differences observed and minimal adverse effects reported. Conclusion: Both microneedling and TCA CROSS are effective and safe in diminishing facial acne scars, yielding similar outcomes between the two treatment groups.